Successful Austerity in the United States, Europe and Japan - Callegari, Giovanni; Batini, Nicoletta; Melina, Giovanni (Washington, D.C. : International Monetary Fund, 2012)
The output effects of 2009 fiscal expansions have been hotly debated. But the discussion of fiscal multipliers is even more relevant now that several European countries have had to quickly retract their stimulus measures in an effort to regain market confidence. Using regime-switching VARs we estimate the impact of fiscal adjustment on the United States, Europe and Japan allowing for fiscal multipliers to vary across recessions and booms. We also estimate ex ante probabilities of recessions derived in association with different-sized and different types of consolidation shocks (expenditure- versus tax-based). We use these estimates to understand how consolidations should be designed to be most effective in terms of permanently and rapidly reducing a country's debt-to-GDP ratio. The main finding is that smooth and gradual consolidations are to be preferred to frontloaded or aggressive consolidations, especially for economies in recession facing high risk premia on public debt, because sheltering growth is key to the success of fiscal consolidation in these cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet